The Christmas spirits on Tradd street [large type] - White, Karen (Karen S.) (White, Karen (Karen S.). Tradd Street series, 2020)
"Melanie Trenholm should be anticipating Christmas with nothing but joy--after all, it's only the second Christmas she and her husband, Jack, will celebrate with their twin toddlers. But the ongoing excavation of the centuries-old cistern in the garden of her historic Tradd Street home has been a huge millstone, both financially and aesthetically. Local students are thrilled by the possibility of unearthing more Colonial-era artifacts at the cistern, but Melanie is concerned by the ghosts connected to it that have suddenly invaded her life and her house--and at least one of them is definitely not filled with holiday cheer ... And these relics aren't the only precious artifacts for which people are searching. A past adversary is convinced there is a long-lost Revolutionary War treasure buried somewhere on the property Melanie inherited--untold riches rumored to have been brought over from France by the Marquis de Lafayette himself and intended to help the Colonial war effort. It's a treasure literally fit for a king, and there have been whispers throughout history that many have already killed--and died--for it. And now someone will stop at nothing to possess it--even if it means destroying everything Melanie and Jack hold dear"--Provided by publisher.